(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
For a long time, proverbs and sayings help us to learn English because these proverbs entered history of the country, their lives, traditions, customs and culture, by the way, they are a good example of the English culture and language. At that time and now proverbs were useful material to show how one thought can be understood in several various ways, and we can distinguish sense of proverbs.